Are There Any Indonesian Philosophers? Dealing with a Common Question and Possible Answers - Al Makin Al Makin (Universitas Islam Negeri Mataram, 2016)
This article is an attempt to expose the idea of, or possibility to reclaim, Indonesian philosophy, but it is not the intention of this article to go into a detailed reading of particular works. It aims at offering a modest proposal, or an outline, sketching many possibilities of reading Indonesian works. It deals with a daunting question often posed by Indonesian students and scholars whether Indonesia can produce a philosopher or philosophical works. This article starts with addressing the question and looks for possible answers through classical Indonesian works not only from writing tradition but also material cultures, such as architectural works. It argues that Indonesian works are materials and sources worth rereading and reinterpreting through which Indonesian philosophers or philosophical works can be reclaimed, or at least unearthed. Although these works may not sound philosophical, the ways in which readers appreciate them can lead to the discovery of a unique Indonesian philosophy. DOI: http://dx.doi.org/10.20414/ujis.v20i1.826